Comparative immune-profiling of tick vaccine formulations and the role of co-infestation with Babesia microti in Ixodes ricinus-infested BALB/c mice - Maritz-Olivier, Christine (University of Pretoria, 2020)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2019.